New records of two appendage bearing ceolomycetes on grasses in Thailand - Goonasekara, Ishani D.; Jayawardena, Ruvishika S.; Saichana, Natsaran (Phytotaxa, 2022)
Grasses are agriculturally, economically and ecologically dominant among plants. Their fungal diversity is fascinating but has been relatively poorly studied or restricted to a few important hosts or pathogens. Therefore, numerous grass-inhabiting fungal species are awaiting discovery or re-study based on morphology and molecular phylogeny. In an ongoing study of grass-inhabiting fungi in Thailand, two interesting saprobic members of Sodariomycetes were collected. Based on morphology, coupled with combined gene analyses of LSU and ITS sequence data, they were identified as Dinemasporium pseudostrigosum and Robillarda africana belonging to Chaetosphaeriaceae and Sporocadaceae, respectively. This is the first report of the two species for Thailand as well as the first record of R. africana occurring on grasses. The newly collected species are compared to other related species and comprehensive descriptions and photo-micrographs are provided.